Konsep Islam Tentang Pelestarian Lingkungan Hidup: Islamic Concept About Environemantal Conservation - saifudin djazuli (Direktorat Jenderal Bimbingan Masyarakat Islam, 2014)
Conservation in the perspective of Islam became an essential part in the concept of worship. Nature conservation established on the concept of balance while human in addition utilizing the environment, expected maintain its sustainability. Islam even mention that the environmental damage caused by the hands of the irresponsible people will be punished and tortured in return. Thus, Islam explicitly ordered mankind to preserve the environment.